DECIPHERING KINETIC, METABOLIC AND ENVIRONMENTAL CONTROLS ON STABLE ISOTOPE FRACTIONATIONS BETWEEN SEAWATER AND THE SHELL OF TEREBRATALIA TRANSVERSA (BRACHIOPODA) - Auclair A.C.; Joachimski M.M.; Lecuyer C. (My University, 2003)
This study presents carbon and oxygen stable isotope data obtained from high-resolution sampling (<500 μm) of the brachiopod terebratalia transversa from san juan islands (washington state, usa). aim this study is to unravel respective effects physiological and environmental controls on stable isotopic composition shell calcite. based an sem shell, a three-dimensional sampling was performed in order investigate carbon oxygen isotope variations along isochrons ontogenetic transects.the primary as well outer part secondary layer display large variable offsets high -7‰ for δ13C and -6‰ for δ18O relative to expected equilibrium values. The significant positive correlations between δ18O and δ13C values indicate that the isotopic compositions of these shell domains are mainly controlled by kinetic isotope fractionation effects. The ontogenetic δ13C and δ18O variations can be used to establish a growth curve of the studied specimen whose age is estimated close to 8 years. The extent of apparent O-18 disequilibrium observed in this study is about as large as any yet measured in any organism, which makes this brachiopod an interesting and important case.The carbon and oxygen isotope compositions increase from the outer towards the inner part of the secondary layer, where they reach values of 0-0.8‰ and -0.8‰ to -0.2‰, respectively. Corresponding calculated temperatures are between 12 and 13.8 °C and fall in the range of seawater temperatures recorded off the San Juan Islands (7-13 °C). These results suggest that the calcite fibres were secreted more and more slowly during the thickening of the shell throughout the animal's life, finally approximating isotopic equilibrium.This study illustrates that the stable isotopic composition of the modern brachiopod T. transversa is predominantly influenced by kinetic fractionation and, to a minor degree, by metabolic effects. Except for the innermost part of the shell, the measured isotope ratios do not reflect environmental conditions during shell precipitation. It remains to be tested by comparable studies whether other modern brachiopod species or even fossil brachiopods reflect comparable fractionation effects. These results point out the need for re-examination of Paleozoic oceanographic conditions.
Keywords: OXYGEN-18; CARBON-13; KINETIC EFFECTS; RESPIRATION; PALEOZOIC; Paleozoic; Палеозой